Demographic Context of Thai-Western Partnerships in Thailand - Phuengsamran, Dusita; Punpuing, Sureeporn; Darawuttimaprakorn, Niphon; Prohmmo, Aree (Journal of Population and Social Studies [JPSS], 2023)
Marriages between Thais and Westerners have become more frequent in Thailand, which could have significant social and economic implications for the country. However, we currently lack information on the exact number of Thai-Western couples and their demographic characteristics. To address this, we conducted a study using Thailand’s 2010 Population Census to explore the scale of Thai-Western partnerships and identify some basic demographic traits of these marriages. Our findings revealed that in 2010, Thai-Western couples made up less than 1% of all married couples. Additionally, more male Westerners partnered with Thai individuals than female Westerners with Thai partners. The nationalities that predominantly formed partnerships with Thais were British, American, and German, comprising more than half of all Westerners in such unions. We also observed that approximately one-third of Westerners in these partnerships were 60 or older, indicating a significant age difference between Western men and their Thai counterparts. Furthermore, most Thai-Westerner couples reside in Bangkok, the capital city of Thailand.